The prevalence of V.ovalifolium in Pulau Dua Nature Reserve was surveyed. This parasite was observed parasitizing on only two host species, Excoecaria agallocha and Thespesia populnea, among 11 potential host tree species in the study area. This phenomenon, contemporarily coined as local host specificity, is complementary to a small endnote on Backer & Bakhuizen van den Brink’s 1965 Flora of Java vol. II. V.ovalifolium’s prevalence is higher as the increase on host tree DBH, as the decrease of i - AGUNG SEDAYU; ALEX SUMADIJAYA (HAYATI Journal of Biosciences, 2012)
The prevalence of V.ovalifolium in Pulau Dua Nature Reserve was surveyed. This parasite was observed parasitizing on only two host species, Excoecaria agallocha and Thespesia populnea, among 11 potential host tree species in the study area. This phenomenon, contemporarily coined as local host specificity, is complementary to a small endnote on Backer & Bakhuizen van den Brink’s 1965 Flora of Java vol. II. V.ovalifolium’s prevalence is higher as the increase on host tree DBH, as the decrease of infested host branch diameter and as the increase of host tree branching order. Two later findings point at Dicaeum trochileum as V.ovalifolium seed disperser among 90 bird species living on the nature reserve.